State of the Union Addresses - Monroe, James, 1758-1831 (Salt Lake City, UT : Project Gutenberg, 2004)
"State of the Union Addresses" by James Monroe is a historical account compiled during the early 19th century, detailing the annual addresses Monroe delivered to Congress. The text encompasses a range of topics reflecting the political, economic, and military state of the United States during Monroe's presidency, highlighting issues with foreign relations, domestic policies, and national progress. The opening of the book introduces Monroe's State of the Union Address delivered on December 12, 1817, where he expresses pride in the nation's prosperity and progress. Monroe addresses the government and citizenry by outlining advancements in agriculture, commerce, and public credit while emphasizing the importance of national unity and defense preparations. He details agreements with Britain regarding naval forces on the Great Lakes and discusses ongoing negotiations with Spain concerning trade and territorial claims. This sets the stage for a comprehensive look into Monroe's administration and thought process during a transformative period in American history. (This is an automatically generated summary.)
Release date is 2004-02-01
Produced by James Linden. HTML version by Al Haines.
Keywords: Presidents -- United States -- Messages; United States -- Politics and government -- Sources